2009
DOI: 10.1089/thy.2008.0384
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Thyrotropinoma Cosecreting Growth Hormone and Follicle-Stimulating Hormone with Low α-Glycoprotein: A New Subentity?

Abstract: This case of plurihormonal thyrotropinoma is unique in having hypersecretion of TSH, GH, and FSH with low alpha-subunit. Such a combination may represent a new subentity of TSHomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Long acting somatostatin analogue drugs reduce TSH secretion and normalize FT4 and FT3 levels in 90% of patients suffering with pituitary TSH secreting tumors (37). In 25 percent of thyrotropinoma cases there is autonomous secretion of a second pituitary hormone (38). One of our 9 patients with recurrent Cushing's syndrome also had the symptoms of central hyperthyroidism with nal diagnosis of plurihormonal pituitary adenoma with expression of ACTH, FSH and TSH (case 7, Table 2).…”
Section: Discussionmentioning
confidence: 85%
“…Long acting somatostatin analogue drugs reduce TSH secretion and normalize FT4 and FT3 levels in 90% of patients suffering with pituitary TSH secreting tumors (37). In 25 percent of thyrotropinoma cases there is autonomous secretion of a second pituitary hormone (38). One of our 9 patients with recurrent Cushing's syndrome also had the symptoms of central hyperthyroidism with nal diagnosis of plurihormonal pituitary adenoma with expression of ACTH, FSH and TSH (case 7, Table 2).…”
Section: Discussionmentioning
confidence: 85%
“…Plurihormonal TSHomas with hypersecretion of GH revealed acromegaly usually masks secondary hyperthyroidism (17,18). A unique study revealed a plurihormonal TSHoma hypersecretion of TSH, GH, and FSH (14). The majority of plurihormonal pituitary tumors may only present with mass tumor effect (headache and visual impairment), without any other symptoms of a functioning pituitary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical symptoms were variable. Some only presented with hyperthyroidism (12,9,14). Simultaneously, some patients showed acromegaly with hyperprolactinemia (11) or hyperthyroidism (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Long acting somatostatin analog drugs reduce TSH secretion and normalize FT4 and FT3 levels in 90% of patients suffering with pituitary TSH secreting tumors (Ben-Shlomo and Melmed 2010 ). In 25% of thyrotropinoma cases, there is autonomous secretion of a second pituitary hormone (Elhadd et al 2009 ). One of our 9 patients with recurrent Cushing’s syndrome also had the symptoms of central hyperthyroidism with final diagnosis of plurihormonal pituitary adenoma with expression of ACTH, FSH, and TSH (case 7, Table 2 ).…”
Section: Discussionmentioning
confidence: 99%